Electroless Nanoplating of Iridium: Template‐Assisted Nanotube Deposition for the Continuous Flow Reduction of 4‐Nitrophenol. Issue 16 (20th August 2020) - Scheuerlein, Martin Christoph; Muench, Falk; Kunz, Ulrike; Hellmann, Tim; Hofmann, Jan P.; Ensinger, Wolfgang
Abstract: Electroless plating is a powerful tool in nanofabrication and is available for many of the noble transition metals. There is, however, a striking lack of electroless plating procedures for the rarer platinum‐group metals. In this work, two plating baths for nanoscale iridium coatings are developed and their conformality and nanofabrication potential are showcased by coating ion‐track‐etched polycarbonate membranes, creating Ir nanotubes in the process. Both plating solutions yield morphologically different deposits, indicating that the microstructure of the film can be tuned by adjusting the composition of the plating bath. The catalytic performance of the deposited materials is investigated by using membrane‐embedded nanotubes as catalysts for the reduction of 4‐nitrophenol and methyl orange by borohydride, showing remarkable activity and stability. Operation in flow‐through configuration, in which the metallized membrane is implemented as a microreactor greatly enhances the interaction with the catalyst surface, considerably increasing product yield. The results highlight the potential of Ir nanoplating for realizing sophisticated nanostructures and heterogeneous catalysts, but also illustrate the intricacies related to the complex chemistry of electroless Ir plating baths. Abstract : Iridium nanoplating : Iridium nanoparticle films are deposited into porous polycarbonate membranes from metastable solutions containing IrCl3, different ligands, and NaBH4, enabling surface‐selective metal reduction while suppressing oxide and metal precipitation during plating. Subsequent removal of the substrate allows the isolation of iridium nanotubes. The coated membranes are implemented as miniaturized flow reactors for the reduction of 4‐nitrophenol, showing remarkable activity and stability.